Hospitalization Rates of Complicated Pneumococcal Community-Acquired Pneumonia is Increasing in Tuscan Children. (October 2013) - Bonsignori, F.; Chiappini, E.; Orlandini, E.; Parretti, A.; Sollai, S.; Resti, M.; Galli, L.; Azzari, C.; De Martino, M.
To provide epidemiological data on community-acquired pneumonia (CAP) and complicated CAP, a retrospective study was conducted on a partially vaccinated paediatric population. Data from children hospitalized for CAP in Tuscan hospitals between January 1 st, 1999 and December 31 st, 2009 were analysed. A total of 5, 450 children with CAP were hospitalized. Annual hospitalization rates for CAP did not change significantly over the study period (χ 2 for trend= 0.652; p=0.419). The total annual hospitalization rate for pneumococcal CAP varied according to age (28.04 per 100, 000 children aged ≤ 5 years, 10.06 per 100, 000 children aged 6–12 years and 0.98 per 100, 000 children aged ≥ 13years). Hospitalization rates for pneumococcal CAP increased from 12.84 (95% CI:7.35–18.34) in 2001 to 45.4 (95%CI:35.93–54.90) per 100, 000 children aged ≤ 5 years in 2009 (p<0.0001). In addition, a significant increase of hospitalization rates for complicated CAP (from 6.07 in 1999 to 13.66 in 2009 per 100, 000 children; P<0.0001) and pneumococcal complicated CAP (from 0.19 in 1999 to 3.41 in 2009 per 100, 000 children) over the study period were highlighted. Our epidemiological data confirm the decision to introduce the PCV13 vaccine, to satisfy the need to prevent a wider group of pneumococcal serotypes.